Work-Life Balance for Department Chairs - Jeff Buller (Academic Chairpersons Conference Proceedings, 2020)
Many chairs feel that the responsibility of the job has completely consumed their lives. Their leadership and management duties leave them with far less time to conduct research, engage with members of their families to the extent they desire, plan their courses, and just sit, think, and catch their breaths. This practical and interactive workshop will explore proven techniques that chairs can use to restore the degree of work-life balance they desire.
Keywords: work-time balance time management stress reduction